Improving Self-Control Through The Traditional Clock Game Method In Children Aged 5-6 Years At Darussalam Pansor Kindergarten In 2024/2025 - Warni, Sitrani; Muhajirin, Muhammad; Mahendra, Juandra Prisma (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to improve the quality and effectiveness of learning activities conducted in the classroom and assist teachers in identifying issues within learning activities and finding effective solutions, particularly in enhancing self-control among children aged 5–6 years using the traditional bakiak game method at Darussalam Pansor Kindergarten, Pansor Village, Pansor Lauk Hamlet, Kayangan Subdistrict, North Lombok Regency. The sample consisted of 20 children, including 7 girls and 13 boys. Self-control is an essential skill that should be developed in children from an early age to help them manage their emotions effectively, thereby enabling them to socialize well with others. The research method employed was a classroom action research design based on the framework proposed by Kemmis and McTgart.The results of the study showed that children's self-control abilities using the traditional bakiak game method reached 20% in the pre-action phase, then reached 65% in cycle I, and finally reached a good score in cycle II, which met the researcher's expected classical completion criteria of 85%.